2020
DOI: 10.1111/jonm.13001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervision: A panacea for missed care

Abstract: Mounting reports of missed nursing care emphasizes the negative implications on patient outcomes, illuminating the stark realities currently facing the profession (Recio-Saucedo et al., 2018; White, Aiken,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
(69 reference statements)
1
21
0
Order By: Relevance
“…Nurse managers must consider ways of fostering an ethical working environment and implementing strategies that support nurses’ well‐being, morale and personal and professional development. For example, clinical supervision is a supportive intervention that can help reduce stress and burnout for nurses (Markey et al., 2020). Providing ethics education and training is also recommended as a means of creating a greater awareness of ethical considerations and supports the application of professional values in daily practice (Poorchangizi et al., 2019).…”
Section: Purpose: Maintaining Ethical Vigilancementioning
confidence: 99%
See 1 more Smart Citation
“…Nurse managers must consider ways of fostering an ethical working environment and implementing strategies that support nurses’ well‐being, morale and personal and professional development. For example, clinical supervision is a supportive intervention that can help reduce stress and burnout for nurses (Markey et al., 2020). Providing ethics education and training is also recommended as a means of creating a greater awareness of ethical considerations and supports the application of professional values in daily practice (Poorchangizi et al., 2019).…”
Section: Purpose: Maintaining Ethical Vigilancementioning
confidence: 99%
“…Nurse managers must consider ways of fostering an ethical working environment and implementing strategies that support nurses' well-being, morale and personal and professional development. For example, clinical supervision is a supportive intervention that can help reduce stress and burnout for nurses (Markey et al, 2020).…”
Section: Purp Os E: Maintaining E Thi C Al Vig Il An Cementioning
confidence: 99%
“…Nurse educators and leaders need to critically examine ways of embedding professional values into every day practice, as a means of fostering moral motivation in the care of culturally diverse patients. Providing opportunities for student and qualified nurses to think about, reflect and discuss practice dilemmas encourages the questioning of the effectiveness of care provided, thus empowering them to make improvements (Markey et al, 2020b). Ultimately, there needs to be a clearer message that substandard and culturally insensitive care will not be tolerated and this requires having more explicit accountability and repercussions.…”
Section: Moral Motivationmentioning
confidence: 99%
“…A systematic review written in 2016 3 demonstrates the importance of clinical supervision; it identified an association between those healthcare professionals that were involved in clinical supervision and an increase in improvement in some care processes. However, there is still an absence of literature demonstrating its outcomes, 15 and although there is a plethora of research that writes about the importance and benefits of clinical supervision, it remains underused 16 . Furthermore, there is limited research conducted on how best to organize and steer clinical supervision within practice; this alongside professionals’ lack of awareness of effective clinical supervision adds to the confusion and lack of use of clinical supervision within healthcare 17 .…”
Section: Introductionmentioning
confidence: 99%